∣ 3 x − ∣ 1 − 2 x ∣ ∣ = 2
Given that the sum of all possible values of x that satisfy the equation above can be expressed in the form n m , where m and n are coprime, positive integers, find the value of m + n .
This problem is part of the set Absolute Value Equations .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f ( x ) = ∣ 3 x − ∣ 1 − 2 x ∣ ∣ .
Case 1: For x < 2 1
f ( x ) = ∣ 3 x − 1 + 2 x ∣ = ∣ 5 x − 1 ∣ ⟹ ⎩ ⎪ ⎨ ⎪ ⎧ For x < 5 1 For 5 1 ≤ x < 2 1 ⟹ f ( x ) = 1 − 5 x = 2 ⟹ f ( x ) = 5 x − 1 ⟹ x = − 5 1 < 5 1 ⟹ 0 ≤ f ( x ) < 2 3 < 2 Accepted No solution
Case 2: For x ≥ 2 1
f ( x ) = ∣ 3 x − 2 x + 1 ∣ = ∣ x + 1 ∣ = x + 1 = 2 ⟹ x = 1 ≥ 2 1 Accepted
Therefore, the sum of solution is 1 − 5 1 = 5 4 ⟹ m + n = 4 + 5 = 9 .
I will here make 2 cases
i) x ≥ 2 1 .
ii) x < 2 1 .
Solving case 1 we get ∣ 3 x + 1 − 2 x ∣ = 2 x + 1 = 2 , x + 1 = − 2 x = 1 , x = − 3 Here we will reject x = − 3 as a solution since it is not in the chosen domain and keep x = 1 .
Now solving case 2 we get ∣ 3 x − 1 + 2 x ∣ = 2 5 x − 1 = 2 , 5 x − 1 = − 2 x = 5 3 , x = − 1 5 Here we will reject x = 5 3 and keep x = 5 − 1 .
So we get the sum of 1 − 5 1 = 5 4 .
Typo in the third line of case 2 solving. You forgot to put the " \textrm{\frac} " before starting the braces for the second solution.
Assume x has a positive value, the equation would then solve for us to obtain x=1.
Assume x has a negative value, the equation would then solve for us to obtain x= -0.2.
Then, add both possible values together and we would obtain 4/5.
Hence, the answer is 4+5=9.
Problem Loading...
Note Loading...
Set Loading...
∣ 3 x − ∣ 1 − 2 x ∣ ∣ = 2 has two solutions, viz.
3 x − ∣ 1 − 2 x ∣ = 2 ⇒ 3 x − 2 = ∣ 1 − 2 x ∣ . . . ( A )
3 x − ∣ 1 − 2 x ∣ = − 2 ⇒ 3 x + 2 = ∣ 1 − 2 x ∣ . . . ( B ) .
Further more, each equation - ( A ) & ( B ) will provide us with 2 solutions each for x . Let's name them x 1 , x 2 , x 3 & x 4 .
(A) ⇒ x 1 = 5 3 , x 2 = 1
(B) ⇒ x 3 = 5 − 1 , x 4 = − 3
x 1 & x 4 are rejected as they do not satisfy the main equation : ∣ 3 x − ∣ 1 − 2 x ∣ ∣ = 2
Therefore, the values of x satisfying the given equation are x 2 & x 3 , which are 1 , 5 − 1 respectively.
⇒ x 2 + x 3 = 5 4 = n m
Therefore, m + n = 4 + 5 = 9 .